Computers Helping People with Special Needs 12th International Conference, ICCHP 2010, Vienna, Austria, July14-16, 2010, Proceedings, Part II - Miesenberger, Klaus; Klaus, Joachim; Zagler, Wolfgang; Karshmer, Arthur; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Welcome to the Proceedings of ICCHP 2010! We were proud to welcome participants from more than 40 countries from all over the world to this year$1 (Bs ICCHP. Since the late 1980s, it has been ICCHP$1 (Bs mission to support and reflect development in the field of (3z(BAssistive Technologies,(3y (BeAccessibility and eInclusion. With a focus on scientific quality, ICCHP has become an important reference in our field. The 2010 conference and this collection of papers once again fulfilled this mission. The International Programme Committee, comprising 106 experts from all over the world, selected 147 full and 44 short papers out of 328 abstracts submitted to ICCHP. This acceptance ratio of about half of the submissions demonstrates our strict pursuit of scientific quality both of the programme and in particular of the proceedings in your hands. An impressive number of experts agreed to organize (3z(BSpecial Thematic Sessions(3y (B(STS) for ICCHP 2010. These STS help to bring the meeting into sharper focus in several key areas. In turn, this deeper level of focus helps to collate a state of the art and mainstream technical, social, cultural and political developments.s
People with Specific Learning and Cognitive Problems: ICT, AT and HCI -- People with Motor Disabilities: HCI and Rehabilitation -- People with Motor Disabilities: How to Improve Text Input -- Deaf and Hard of Hearing People: Accessible Information and Education -- Deaf People: AT for Sign Language -- Blind and Partially Sighted People: Mobility and Interaction without Sight -- Blind and Partially Sighted People: Rehabilitation and Social Skills -- Blind and Partially Sighted People: HCI -- Blind and Partially Sighted People: Access to Mathematics -- Blind and Partially Sighted People: Designing Haptic Interaction for a Collaborative World -- Blind and Partially Sighted People: Three-Dimensional Tactile Models for Blind People and Recognition of 3D Objects by Touch -- Ageing: HCI Usability (HCI4AGING).
Keywords: Computer science; Multimedia information systems; User interfaces (Computer systems).; Computer graphics; Computers and civilization; Computer engineering; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Computer Engineering; Computers and Society; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Electronic books